Analyzing Banking Sector Risk and Capital Allocation: A Study on the Improvement of Risk-Weighted Assets and CRAR Compliance in 2023 - Shuvo Kumar Mallik (HM Journals, 2024)
This study examines the improvement in banking sector risk, measured by the Risk-Weighted Assets (RWA) density ratio, in 2023. It highlights the significant growth in RWA of credit risk compared to market and operational risks, and notes the banking industry's increased capital requirements despite a slight decrease in rated exposures as a percentage of total exposure. The overall Capital to Risk-weighted Asset Ratio (CRAR) surpassed the threshold, ensuring regulatory compliance. The analysis categorizes banks into five groups based on inherent features, ownership structure, and business models, providing insights into risk and capital allocation according to BASEL III.